FEATURES OF STUDENTS-PSYCHOLOGISTS AUTHORITARIAN PERSONALITY - Москаленко, Вікторія Василівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article is devoted to the theoretical and experimental study of the psychological features of authoritarianism of Ukrainian students. In the article the author raises the questions of the particular relevance of research of this problem in modern Ukraine. Since the student’s age is an indicator of the formation of positive personality traits, our research focuses on the study of personal characteristics of the authoritarianism of Ukrainian students of the first and third years of the Kharkiv National University named after VN Karazin. The main tasks of the article were to study three main indicators of authoritarianism, namely, Machiavellianism, fascism and anti-democracy, as well as a comparative analysis of these indicators among first-year students and third-year students of the Faculty of Psychology of the Kharkov National University. As a result of the study, the main features of the authoritarian personality of Ukrainian students were singled out, among them a low level of Machiavellianism, dogmatism, the identification of the leader with the state, the cult of power and the fear of responsibility. In addition, students of the third year of pain expressed dependence on external forces than the first-year students. Students of both the first and third course are not attached to the fascist ideology. Differences in the indicators of Machiavellianism and fascism among students of first-year psychologists with third-grade students are insignificant. However, the differences in comparative values for the factor of authoritarianism are significant, third-year students are more susceptible to psychological manifestations of an authoritarian personality